Inducible Beta-Lactamase Activity of Nosocomial Pseudomonas Aeruginosa Strains - Berktaş, Mustafa; Güdücüoğlu, Hüseyin; Çıkman, Aytekin; Parlak, Mehmet; Yaman, Görkem (Fırat University, 2011)
Objective: Inducible beta-lactamase (IBL) presenting Pseudomonas aeruginosa strains can lead to inadequate treatment because of resistance to many beta-lactam antibiotics and cause serious clinical problems. In this study, we aimed to determine the presence of IBL and antibiotic resistance rates of nosocomial Pseudomonas aeruginosa strains. Materials and Methods: The IBL production were investigated in 87 P. aeruginosa strains which were isolated between October 2008 and November 2009 in our laboratory and defined as nosocomial isolates according to CDC criteria. Susceptibility testing of antipseudomonal antibiotics were performed with Phoenix automated microbiology system (Becton-Dickinson, USA). Results: Among 87 strains isolated from various clinical specimens 64 (74%) P. aeruginosa strains were detected positive for IBL production. Resistance rates for antipseudomonal antibiotics were 11% to amikacin, 38% to ciprofloxacin, 47% to ceftazidime, 51% to levofloxacin, 60% to meropenem, 66% to piperacillin-tazobactam, 71% to imipenem and gentamicin, 72% to aztreonam, 74% to piperacillin, and 76% to cefepime. Conclusion: Because of high incidence of IBL production and antibiotic resistance of P. aeruginosa strains in our hospital, these findings be taken into account can be benefit when planning empirical therapy.

Amaç: Çalışmada, indüklenebilir beta-laktamaz (İBL) varlığında ciddi klinik sorunlara yol açan, birçok beta-laktam antibiyotiğe direnç geliştirerek tedavi yetersizliğine neden olabilen hastane kaynaklı Pseudomonas aeruginosa suşlarında, İBL varlığı ile antibiyotik direnç oranlarının belirlenmesi amaçlanmıştır. Gereç ve Yöntem: Ekim 2008 - Kasım 2009 tarihleri arasında laboratuvarda izole edilen ve CDC kriterlerine göre hastane infeksiyonu etkeni olarak tanımlanan 87 P.aeruginosa suşunda İBL üretimi araştırıldı; antipsödomonal antibiyotiklere karşı duyarlılık testleri Phoenix otomatize mikrobiyoloji sistemi (Becton Dickinson- USA) ile yapıldı. Bulgular: Çeşitli klinik örneklerden izole edilen 87 P.aeruginosa suşunun 64'ü (%74) İBL pozitif olarak belirlendi. P.aeruginosa suşlarının antipsödomonal antibiyotiklere direnç oranları; amikasine %11, siprofloksasine %38, seftazidime %47, levofloksasine %51, meropeneme %60, piperasilin-tazobaktama %66, imipenem ve gentamisine %71, aztreonama %72, piperasiline %74, sefepime %76 olarak tespit edildi. Sonuç: Hastanemizde P.aeruginosa suşlarında yüksek İBL üretim sıklığı ve antibiyotik direnci nedeniyle ampirik tedavi planlanırken bu bulguların dikkate alınması yarar sağlayacaktır.
Nozokomiyal Pseudomonas Aeruginosa Suşlarında İndüklenebilir Beta-Laktamaz Aktivitesi